The Influence of Managerial Skills and Human Resource Development on MSME Development in Girikerto Village, Sleman Regency - Dinda Amelia Suci; Aris Wahyu Kuncoro (Golden Ratio of Data in Summary, 2026)
This study aims to examine how managerial skills, individual abilities, and human resource development contribute to the development of Micro, Small, and Medium Enterprises (MSMEs) in Girikerto Village, Sleman Regency, Yogyakarta. The research addresses the question of whether improvements in managerial competence and systematic human resource programs can strengthen MSME performance and sustainability. The study employed a quantitative approach using multiple linear regression analysis to measure the influence of each variable. The sample consisted of all 45 MSME actors in Girikerto Village, selected through a saturated sampling technique. Data were collected through structured questionnaires using a five-point Likert scale and analyzed with SPSS version 25. The findings reveal that managerial skills, individual abilities, and human resource development each have a significant and positive impact on MSME development. Together, these factors substantially enhance business resilience, competitiveness, and independence. The results underscore the importance of continuous managerial capacity building, skill-based training, and systematic human resource improvement to support sustainable local economic growth and policy formulation for rural MSME advancement.